Boundary-Crossing and Integration: Strategies for Cultivating Interdisciplinary Competence in Master of Education Programs at Top-Tier Universities in the United States - HOU Yanan; LIU Junren (Jiaoshi jiaoyu xuebao)
Master of Education (M.Ed.) program at top-tier universities in the United States exhibits distinctive characteristics. The objectives of the program emphasize interdisciplinary competence, and aims to equip graduates with cross-disciplinary knowledge, and critical reflection skills who can become educational leaders in educational reform. The curriculum design is centered on interdisciplinary training, incorporating interdisciplinary courses, elective courses, and optional concentration to facilitate interdisciplinary learning. The instructional approach focuses on enhancing interdisciplinary lite-racy, with theme-based and problem-based teaching methods integrated throughout the entire training process. Drawing on this experience, M. Ed. in comprehensive universities in China can target training objectives, curriculum design, and instructional methods to optimize the cultivation and further enhance education quality. Three strategic improvements are proposed. First, adopting an integrative educational philosophy to target interdisciplinary training. Second, restructuring cross-disciplinary system by refining curricula. Third, pedagogical innovation by implementing theme-based and problem-oriented instructional designs.